Reductive Cross-Coupling of Vinyl Electrophiles - Pang, Xiaobo; Peng, Xuejing; Shu, Xing-Zhong (Synthesis, 2020)
The synthesis of alkenes (olefins) is a central subject in the synthetic community. The transition-metal-catalyzed reductive cross-coupling of vinyl electrophiles has emerged as a promising tool to produce alkenes with improved flexibility, structural complexity, and functionality tolerance. In this review, we summarized the progress in this field with respect to cross-electrophile couplings and reductive Heck reactions using vinyl electrophiles.1 Introduction2 Cross-Electrophile Coupling of Vinyl Electrophiles3 Reductive Heck Reaction of Vinyl Electrophiles4 Summary and Outlook
Keywords: alkenes; cross-coupling; reductive coupling; cross-electrophile; Heck reaction; vinylation; nickel; cobalt